1997
DOI: 10.1136/jnnp.63.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral blood flow and vasoreactivity in response to acetazolamide in patients with transient global amnesia

Abstract: Objective-Previousreports about changes in cerebral blood flow (CBF) in transient global amnesia disclosed decreased flow in some parts of the brain. However, CBF analyses in most reports were qualitative but not quantitative. The purpose of this study was to determine changes in CBF in transient global amnesia. Methods-The CBF was measured and the vasoreactive response to acetazolamide was evaluated in six patients with transient global amnesia using technetium-99m hexamethylpropylene amine oxime singlephoton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Different results and interpretations of DWI lesions were given: DWI abnormalities in TGA did not resemble DWI findings in TIA in terms of time course delay, size of lesion and diffusion coefficient values [5,6,7,8,9,10,14]. Moreover, studies supported the hypothesis that vasospasms due to impaired vasoreactivity may trigger TGA [12,13]. …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Different results and interpretations of DWI lesions were given: DWI abnormalities in TGA did not resemble DWI findings in TIA in terms of time course delay, size of lesion and diffusion coefficient values [5,6,7,8,9,10,14]. Moreover, studies supported the hypothesis that vasospasms due to impaired vasoreactivity may trigger TGA [12,13]. …”
Section: Discussionmentioning
confidence: 76%
“…Different neuroimaging findings have been conducted to elucidate the different pathogentic mechanisms in patients with TGA. Several studies suggested that arterial-inflow changes as related to venous incompetence trigger a vasoreactive arterial response [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Findings from previous functional imaging studies of TGA patients have been inconsistent and include abnormalities in perfusion of the temporal lobes (Asada et al, 2000; Evans et al, 1993; Jung et al, 1996; Matsuda et al, 1993; Schmidtke et al, 2002; Stillhard et al, 1990; Strupp et al, 1998; Tanabe et al, 1991; Warren et al, 2000), thalamus (Goldenberg et al,1991; Sakashita et al,1997; Schmidtke et al, 2002), and striatum (Baron et al, 1994; Schmidtke et al, 2002). Although most studies of TGA have reported decreased perfusion, hyperperfusion in persons with TGA has also been reported in a handful of studies, particularly in the hippocampus, amygdala, and thalamus of the left hemisphere (Asada et al, 2000; Jung et al, 1996; Matsuda et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the head of the hippocampus may be more susceptible to venous congestion due to the limited outflow tracts available. Although most patients with TGA showed regional hypoperfusion [4][5][6][7][8][9][10][11][12][13][14], in a few patients in whom SPECT was performed during or immediately after the episode of TGA, there was transient hyperperfusion of the medial temporal or occipitocerebellar areas [10,36,37]. This discrepancy between the results of previous SPECT studies may be due to different timings of the SPECT scans with respect to the chronology of each individual attack [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating regional cerebral blood flow in TGA via single photon emission computed tomography (SPECT) have noted mesiotemporal hypoperfusion with or without the concomitant involvement of various cortical, subcortical and cerebellar structures [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%